The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jbl.12210
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Right Delivery Option for You? Consumer Preferences for Delivery Attributes in Online Retailing

Abstract: Nowadays, online retailers are offering a variety of delivery options consisting of varying combinations of delivery attributes. This study investigates how consumers value these delivery attributes (e.g., delivery speed, time slot, daytime/evening delivery, delivery date, and delivery fee) when selecting a delivery option for their online purchases. Mental accounting theory is used to frame the research and to suggest how mental accounts for money, time, and convenience influence consumer preferences for onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
143
4
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(166 citation statements)
references
References 83 publications
6
143
4
13
Order By: Relevance
“…Considering the recent literature on online shopping [14,20,21], we include the following four product attributes with their levels:…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…Considering the recent literature on online shopping [14,20,21], we include the following four product attributes with their levels:…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“… Nguyen et al (2019) used cluster analysis to identify three consumer types that showed preferences for online purchases. These segments were classified as price-oriented, time-and-convenience-oriented, and value-for-money-oriented.…”
Section: Introduction and Background Contextmentioning
confidence: 99%
“…Sistem informasi akuntasi bisnis di e-commerce tidak selalu diterima oleh pe rilaku manusia yang menggunakan sistem informasi akuntansi tersebut (Dagiliene & Šutiene, 2019;Hardanti, Subekti, & Mardia ti, 2014;Hariyati, Tjahjadi, & Soewarno, 2019). Perilaku seseorang menggunakan tek nologi mampu dijelaskan oleh salah satu teori psikologi yaitu teori utama penerimaan dan penggunaan teknologi (Mhina, Johar, & Alkawaz, 2019;Nguyen, Leeuw, Dullaert, & Foubert, 2019). Teori ini menjelaskan pene rimaan penggunaan teknologi pada diri se seorang oleh variabel ekspektasi usaha, ek spektasi kinerja, pengaruh/dorongan sosial, dan kondisi/keadaan fasilitas yang akan mempengaruhi intensi keperilakuan sese orang dan diaktualisasikan kepada perilaku penggunaan suatu teknologi tertentu (Ven katesh, Thong, & Xu, 2016).…”
unclassified